Utilizing Statistical Models for Proposing Hybrid Noise Approach of Image Encryption - A. Neamah, Irtefaa; Rustum Mohammed, Hind (International Journal of Engineering and Technology, 2018)
A proposed strategy for an encryption of image based on image noise by statistical models is represented in this paper. An image encryption algorithm has been designed and simulated for some of the common various types of image noise. The proposed method (Hybrid Noise) consisting of a composition of more than one of probability density functions.Further, the hybrid approach has been compared with some standard noise types such as Gaussian, salt, and pepper, and speckle noise based on some of the performance scales like Peak Signal to Noise Ratio, variance and standard deviation and other comparison tools. The results show that our hybrid method has more security of image with less Peak Signal to Noise Ratio values, which means high noise level.Â Â